2016
DOI: 10.1002/jmr.2601
|View full text |Cite
|
Sign up to set email alerts
|

A biophysical and computational study unraveling the molecular interaction mechanism of a new Janus kinase inhibitor Tofacitinib with bovine serum albumin

Abstract: The interaction of a recently certified kinase inhibitor Tofacitinib (TFB) with bovine serum albumin (BSA) has been studied, by spectroscopic and molecular docking studies. Spectrofluorimetric measurements at 3 different temperatures (288, 298, and 310 K) showed that TFB quench the intrinsic fluorescence of BSA upon forming a nonfluorescent complex. The intrinsic fluorescence data showed that TFB binds to BSA with binding constant (K ) of approximately 10 M , affirming a significant affinity of TFB with BSA. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 59 publications
3
8
0
Order By: Relevance
“…The donor (BSA) to acceptor (4MMC) distance ( r ) is much less than 8 nm, which suggested that there is a great probability of transfer of energy from the Trp residues of the BSA to the 4MMC with high probability . Thus, the results again strongly support that the ground‐state complex gets formed between the 4MMC and BSA through the energy transfer . This result is in good agreement with our study state and time‐resolved fluorescence spectroscopy results.…”
Section: Resultssupporting
confidence: 87%
“…The donor (BSA) to acceptor (4MMC) distance ( r ) is much less than 8 nm, which suggested that there is a great probability of transfer of energy from the Trp residues of the BSA to the 4MMC with high probability . Thus, the results again strongly support that the ground‐state complex gets formed between the 4MMC and BSA through the energy transfer . This result is in good agreement with our study state and time‐resolved fluorescence spectroscopy results.…”
Section: Resultssupporting
confidence: 87%
“…As shown in Figure , 2 negative minima in far UV range of 208 and 222 nm clearly indicate the α‐helix nature of protein as shown by others . The CD spectrum of native protein, ie, BLC, shows 2 characteristic peaks at or around 222 (due to n → pi* transition) and 208 nm (due to pi → pi* transition), signifying the presence of α‐helical structure of BLC as observed by Abdelhameed et al The binding of clofazimine with BLC leads to an enhancement in the negative minima at 208 and 222 nm, indicating the induction of α‐helix. Further, far‐UV CD spectra obtained even after clofazimine addition in a ratio (1:10) were identical in shape, showing the presence of α‐helices predominantly in BLC.…”
Section: Resultssupporting
confidence: 51%
“…Transfer of energy was successful when the quantum yield of the donor molecule was high, when both the molecules had a proper orientated transition dipole moment and when the distance between donor‐to‐acceptor molecules was less than 8 nm . A distance between donor and acceptor molecule of less than 8 nm also signified that fluorescence quenching during drug–protein interaction was of the static type . FRET parameters such as overlap integral (J) obtained from Equation , energy transfer (E) obtained from Equation , critical distance (R o ) calculated from Equation and the distance between HAs and BSA (r) evaluated from Equation are listed in Table .…”
Section: Resultsmentioning
confidence: 99%